PENGUATAN KAPASITAS MARKETING PRODUK INDUSTRI KREATIF BERBASIS MARKETING SYARIAH DAN PEMANFAATAN IT DI SLEMAN - Kholis, Nur; Priyadi, Unggul; Hendrik, Hendrik (Millah: Journal of Religious Studies, 2014)
Daerah Istimewa Yogyakarta province has a strategic position in developing creative industries. One of the districts that support these creative industries is Sleman. However, SMEs in Sleman district still largely prosperous, because they do not take more advantage of IT development to increase sales. The problems of this study, how to construct the marketingmodel for product of creative industries that adopted the principles of sharia marketing by utilizing the E-Commerce portal to increase revenues and competitiveness of creative industries in Sleman at the level of domestic market and international market. This research has produced an e-commerce portal (http://jogjakreatif.com) equipped with SMS gateway that enables traders of creative industries in Sleman to promote and conduct transactions with customers on line-based or sms. Through this facility, traders are not required to check transaction activity every time, but they can obtain latest information regarding transactions via email and sms.